Effect of biodegradable versus nondegradable nasal packings in the outcome of functional endoscopic sinus surgery: clinical and histopathological study - Ayman Al-Madani; Ahmed Youssef; Ayman Abduljalil; Hoda Khalifa; Mohamed Zahran (The Egyptian Journal of Otolaryngology, 2018)
Abstract Background Nasal packing has been used to prevent bleeding and formation of adhesions between the middle turbinate and lateral nasal wall. There has been a debate whether biodegradable packing might improve the outcome, or could a nondegradable dressing offer a better course after endoscopic sinus surgery. Objective To compare the effect of biodegradable versus nondegradable nasal packings on the outcome of endoscopic sinus surgery on clinical, endoscopic, and histopathologic basis. Patients and Methods Fifty patients with bilateral chronic rhinosinusitis of the same extent of sinus affection were enrolled in this study. None of them was a revision case. All patients had bilateral functional endoscopic sinus surgery by the same surgeon using the same technique of powered microdebrider utilization. At the end of the procedure, the operative cavity of each patient was randomly packed with Merocel as a nondegradable material on one side and a biodegradable material on the other side. We assessed the patients regarding immediate postoperative symptoms and endoscopic follow-up after 1- and 3-month postoperatively including biopsy taking for histopathological examination. Results Postoperative bleeding and patient discomfort were significantly higher in the nondegradable packing side, while biodegradable packing has caused significantly more edema. Merocel packed sides showed better epithelial restoration with marked epithelial hyperplastic changes and more goblet cells than the biodegradable sides. This difference was statistically significant 1-month postoperatively, but turned nonsignificant 3-month postoperatively. Conclusions Biodegradable nasal packing can offer patients a good quality of life during the early recovery period without beneficial or detrimental effects on postoperative mucosal healing. Nondegradable packs offer less post-functional endoscopic sinus surgery edema providing better aeration and rapid wound healing.